The attitude of alcohol-addicted parents towards further education of their children - Ławska, Wioletta; Zięba, Mara; Dębska, Grażyna; Łyżnicka, Maria (Polish Journal of Public Health, 2010)
Introduction. As the world is changing, the attitude towards further education is changing as well. Most people aim at getting good qualifications and acquire knowledge at different levels. Parents motivate their children by convincing them that good education may create a chance for having a better job or being independent. Children from supportive families where parents are role models for them are much happier, and this educational aim is easier to achieve. Aim. The aim of the study is to present the attitude of alcohol-addicted parents, who are under treatment, towards further education of their lower secondary school children. What is more, the thesis is going to show what influence alcoholism in families has on the children. Material and methods. The research was done among the people who are patients in Alcohol Addiction Treatment and Withdrawal Symptoms Departments in Nowy Targ. The tool used for the research was a CAGE survey and an author-designed questionnaire addressed to alcohol-addicted parents. The head of the departments, the manager of the hospital in Nowy Targ, as well as the patients, agreed to the research. Results and conclusions. All the respondents are aware of their addiction to alcohol. Alcohol addicted parents want their children to continue education after the lower secondary school because, in their opinion, education is important in everybody’s life. According to the respondents, alcoholism of parents exerts a negative influence on ambitions of children. The majority of the respondents think that children of alcohol-addicted people are unhappy, however, they do not confirm this opinion speaking about their own children and claim that they are safe and happy. According to the respondents, the level of education does not affect the quantity of alcohol intake and the awareness of harmfulness of this addiction.